Income Disparity, Uneven Economic Opportunities, and Verifiability - Otaki, Masayuki (Advances in Social Sciences Research Journal, 2014)
The function of income in educational investment is considered under asymmetric information on individuals’ effort. High income strengthens deep commitment to investment, and hence facilitates access to the capital market. Low income individuals tend to be excluded for the same reason even though they have the same abilities as wealthy individuals. Thus, disparity of income produces uneven economic opportunities. Some income redistribution policy is necessary to cure this social inefficiency. The expenditure of transferred income should, however, be limited to educational investment to avoid wasteful consumption. Keywords: Educational Investment, Economics, Income Disparity